Of two minds [videorecording (DVD)] - Klein, Lisa (Lisa J.); Blush, Doug; Davis, Carlton; Keating, Cheri; Peterson, Michael; Spikol, Liz (Docuramafilms : Distributed in the U.S. by New Video, 2013)
Profiles four individuals living with bipolar disorder, a condition that afflicts over five million Americans.